Lymph nodes' evaluation in relation to colorectal cancer staging among African Americans. Issue 1 (December 2015) - Ashktorab, Hassan; Ogundipe, Temitayo; Brim, Hassan; Shahnazi, Anahita; Laiyemo, Adeyinka; Lee, Edward; Shokrani, Babak; Nouraie, Mehdi
Abstract Background Lymph nodes' examination in colorectal cancer (CRC) resection specimens is an important determinant that aids in the accuracy of CRC staging and treatment outcomes. Current guidelines call for the examination of at least 12 lymph nodes (LN) in resected specimens in order to establish accurate staging. Aim To investigate lymph nodes' examination protocol as it relates to accurate CRC staging. Methods We reviewed 216 African American CRC patients from 1996–2013 who underwent CRC resection and met inclusion criteria for this study. The number of retrieved LNs, length of resected specimens, tumor grade, stage, location, size and histology were examined. Results The cohort study was made of 49 % males, median age was 63 years and 45 % of patients were at stage III and IV. The median (IQR) number of examined LNs was 15 (10–22) and the rate of patients with more than 12 examined LNs was 64 %. There was a gradual increase in the percentage of patients with adequate number (>12) of examined LNs during the study period (from 60 % in 1996–2000 to 84 % in 2010–2013 period, P  = 0.014). Adequate LNs resection was neither associated with shift of stage from II to III (P  = 0.3) nor with the changes from stage IIIa to IIIc (P  = 0.9). Metastatic LNs were observed in 8 % of samples with LNs (>12) vs. 13 % of samples with <12 examined LNs (P  = 0.1). Patients that had pre-surgical treatment (chemotherapy and radiotherapy) before surgery had <12 LNs examined. There was also a trend of having more examined lymph nodes in large tumors. Conclusions Our study shows that there has been an increase in the number of lymph nodes examined in CRC resections since the advent of the current quality initiative. However this increase does not seem to affect the stage or percentage of metastatic lymph nodes' detection in CRC patients.